2007
DOI: 10.1210/en.2007-1292
|View full text |Cite
|
Sign up to set email alerts
|

The Murine Glucagon-Like Peptide-1 Receptor Is Essential for Control of Bone Resorption

Abstract: Gastrointestinal hormones including gastric inhibitory polypeptide (GIP), glucagon-like peptide (GLP)-1, and GLP-2 are secreted immediately after meal ingestion, and GIP and GLP-2 have been shown to regulate bone turnover. We hypothesize that endogenous GLP-1 may also be important for control of skeletal homeostasis. We investigated the role of GLP-1 in the regulation of bone metabolism using GLP-1 receptor knockout (Glp-1r ؊/؊ ) mice. A combination of bone density and histomorphometry, osteoclast activation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
226
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(240 citation statements)
references
References 37 publications
10
226
1
3
Order By: Relevance
“…It has been shown that GLP1-R is also expressed in C cells of the thyroid gland and exerts, when activated by GLP-1 or its stable analogues, a stimulating effect on calcitonin secretion in rodents (63,64), a potent inhibitor of bone resorption. As proposed by Yamada et al (29), GLP-1 agonist effects on bone might be indirect rather than direct, acting mainly by targeting calcitonin secretion from the thyroid to modulate bone turnover. Our data indicate that Ex-4 stimulates calcitonin secretion and thus can induce an inhibition of resorption.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…It has been shown that GLP1-R is also expressed in C cells of the thyroid gland and exerts, when activated by GLP-1 or its stable analogues, a stimulating effect on calcitonin secretion in rodents (63,64), a potent inhibitor of bone resorption. As proposed by Yamada et al (29), GLP-1 agonist effects on bone might be indirect rather than direct, acting mainly by targeting calcitonin secretion from the thyroid to modulate bone turnover. Our data indicate that Ex-4 stimulates calcitonin secretion and thus can induce an inhibition of resorption.…”
Section: Discussionmentioning
confidence: 96%
“…Mice with homozygous deletion of the pancreatic GLP-1 receptor develop cortical osteopenia and bone fragility as well as increased osteoclastic bone resorption that might be due to a reduction in thyroid calcitonin secretion (29). Despite a few studies showing a beneficial effect of GLP-1 agonists on bone architecture, the mechanisms by which GLP-1 regulates bone turnover are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a model of GLP1 signaling deficiency, Yamada et al (2008) reported that Glp1r knockout mice exhibit a trend for lower trabecular bone mass in the proximal metaphysis of the tibia. These authors also reported reduction in cortical bone mineral density (BMD) as evidenced by an experimental computed tomography (CT)-based densitometry.…”
mentioning
confidence: 99%